การศึกษาปัจจัยที่มีความสัมพันธ์กับภาวะซึมเศร้าของผู้สูงอายุ วิถีสังคมพหุวัฒนธรรม จังหวัดยะลา - สุนทรนนท์, ธวัชชัย (Journal of Buddhist Education and Research (JBER), 2024)
This study is a descriptive research study with the objective of studying factors related to depression among the elderly in a multicultural society in Yala Province. Members of the Elderly Club in the Cultural Society in Kota Bharu Sub-district, Raman District, Yala Province, 95 people, questionnaire tool Confidence was determined by Cronbach's alpha coefficient method, which was equal to.88. The data was analyzed by a ready-made computer program. The statistics used were percentage, mean, and standard deviation. The relationship was analyzed using Pearson's correlation coefficient statistic. The results showed that most of the samples were female, 70.5% aged 60-70 years, 62.1% followed by 71-80 years, and 24.2% average age was 70.37 years old. Most of the monthly income was less than 1500 baht, or 37.9% of the average income per month. Buddhists make up 56.8% of the population, while Muslims make up 43.2%; married people make up 52.6% of the population.